2019
DOI: 10.1242/dev.171256
|View full text |Cite
|
Sign up to set email alerts
|

Response of epithelial cell and tissue shape to external forces in vivo

Abstract: How actomyosin generates forces at epithelial adherens junctions has been extensively studied. However, less is known about how a balance between internal and external forces establishes epithelial cell, tissue and organ shape. We used the Drosophila egg chamber to investigate how contractility at adherens junctions in the follicle epithelium is modulated to accommodate and resist forces arising from the growing germ line. We found that between stages 6 and 9, adherens junction tension in the postmitotic epith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
4
18
0
Order By: Relevance
“…7A,D), suggesting that cortical tension in FCs is decreasing during this interval. This notion was consistent with decreasing levels of the tension-sensitive protein vinculin (vinculin-GFP; Maartens et al, 2016) at FC junctions from stage 6 to stage 9 (data not shown) and with direct measurements of cortical tension by laser ablation experiments (Balaji et al, 2019). We hypothesized that a decrease in cortical tension could play a role in initiating patency.…”
Section: Actomyosin Contractility Regulates Opening Of Verticessupporting
confidence: 85%
“…7A,D), suggesting that cortical tension in FCs is decreasing during this interval. This notion was consistent with decreasing levels of the tension-sensitive protein vinculin (vinculin-GFP; Maartens et al, 2016) at FC junctions from stage 6 to stage 9 (data not shown) and with direct measurements of cortical tension by laser ablation experiments (Balaji et al, 2019). We hypothesized that a decrease in cortical tension could play a role in initiating patency.…”
Section: Actomyosin Contractility Regulates Opening Of Verticessupporting
confidence: 85%
“…7K-L). This was associated with a conspicuous change in the morphology of AJs, which were straight in control FCs, but corrugated in MLCK-expressing FCs (Fig 7K',L'), suggesting that MLCK-induced myosin contractility led to an increase in cortical tension, consistent with the findings of (Balaji et al, 2019). Strikingly, FCs in MLCK-expressing follicles failed to round up and instead maintained their hexagonal shape at stage 10A, and showed a strong reduction in the size of intercellular openings (Fig.…”
Section: Actomyosin Contractility Regulates Opening Of Verticessupporting
confidence: 82%
“…7A,D), suggesting that cortical tension in FCs is decreasing during this interval. This notion was consistent with decreasing levels of the tension-sensitive protein vinculin (vinculin-GFP; Maartens et al, 2016) at FC junctions from stage 6 to stage 9 (data not shown) and with direct measurements of cortical tension by laser ablation experiments (Balaji et al, 2019). We hypothesized that a decrease in cortical tension could play a role in initiating patency.…”
Section: Actomyosin Contractility Regulates Opening Of Verticessupporting
confidence: 74%
“…Furthermore, cell apices in ncd::γ-tubulin-EGFP placodes often showed a convoluted apical junctional morphology ('wavy' junctions; Fig. 4a-e), that is indicative of strong, possibly excessive, apical constriction 31,32 . In line with this finding, cells showed more constricted apices compared to control (Fig.…”
Section: Resultsmentioning
confidence: 99%